2011
DOI: 10.1179/143307511x12998222918958
|View full text |Cite
|
Sign up to set email alerts
|

Molten salt synthesis of LiGd0·01Mn1·99O4 using chloride–carbonate melt

Abstract: Gadolinium substituted LiMn 2 O 4 powders have been synthesised by molten salt route for application in lithium batteries. The thermal behaviour of precursor salts has been studied using thermogravimetry and differential thermal analyses. The formation of the compound is in the temperature range of 600-700uC. X-ray powder diffraction pattern confirms the presence of single phase cubic structure of LiGd 0?01 Mn 1?99 O 4 . The lattice parameter is found to be a58?2539 Å . The stretching vibrations of the metal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…A similar explanation can be found in the literature. 43 When Mn 3+ /Mn 4+ ions are partially substituted by Gd 3+ ions, they cause Mn-site disorders in LMO, resulting in anomalous shifting of Raman modes toward higher frequencies (blue shift), and the rapid absence of certain modes, as shown by X-ray diffraction. In addition, components such as the binding strength force constant and change in effective mass can affect Raman mode shifting.…”
Section: Resultsmentioning
confidence: 99%
“…A similar explanation can be found in the literature. 43 When Mn 3+ /Mn 4+ ions are partially substituted by Gd 3+ ions, they cause Mn-site disorders in LMO, resulting in anomalous shifting of Raman modes toward higher frequencies (blue shift), and the rapid absence of certain modes, as shown by X-ray diffraction. In addition, components such as the binding strength force constant and change in effective mass can affect Raman mode shifting.…”
Section: Resultsmentioning
confidence: 99%
“…The octahedral MnO 6 structure becomes increasingly distorted, reducing the stability, adsorbent capacity, and durability, and causing considerable water pollution (Jin et al, 2018;Weng et al, 2020). To combat this dissolution phenomenon, many authors have experimented with replacing the Mn 3+ with: divalent cobalt (Co 2+ ), nickel (Ni 2+ ), and magnesium (Mg 2+ ); trivalent chromium (Cr 3+ ), aluminum (Al 3+ , and iron (Fe 3+ ); and, other rare-earth ions (Malyovanyi et al, 2003;Ein-Eli et al, 2005;Eftekhari et al, 2006;Wu et al, 2007;Iqbal and Ahmad, 2008;Amaral et al, 2010;Sakunthala et al, 2010;Wu et al, 2010;Helan et al, 2011;Xu et al, 2011;Xu et al, 2016). LMO-type precursors doped with Fe 3+ , antimony Sb(v), and Al 3+ demonstrated the highest Li + extraction capacity with minimal Mn dissolution.…”
Section: + Manganese Oxide-type Lithium-ion Sievesmentioning
confidence: 99%
“…One of the waysi s to substitute Co 3 + ,T i 2 + ,A l 3 + ,C r 3 + ,a nd Gd 3 + in place of Mn ions,w hich cause disproportion reactions. [9][10][11][12][13] Although the dopinga pproachi mproves the structurals tability,i tr educes the initial capacity seriously.O nt he other hand, surface coating with metal oxides is another methodt or educe the capacity fade of LiMn 2 O 4 .M any oxides,s uch as MgO, [14] Mn 2 O 3, [15] CeO 2 , [16] VO x , [17] ZrO 2 , [18] Al 2 O 3 , [19] and TiO 2, [20] have been reported to be effective to minimize the contact area of the LiMn 2 O 4 particles/electrolytea nd decrease the dissolution of manganese into the electrolyte. Recently,L i et al [19] reported that Al 2 O 3 -coated LiMn 2 O 4 experienced a7 6% capacity retention after 25 cycles,w hich is much better than bare LiMn 2 O 4 (57 %).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the capacity fading problem, two main attempts and methods have been applied. One of the ways is to substitute Co 3+ , Ti 2+ , Al 3+ , Cr 3+ , and Gd 3+ in place of Mn ions, which cause disproportion reactions . Although the doping approach improves the structural stability, it reduces the initial capacity seriously.…”
Section: Introductionmentioning
confidence: 99%